OPTIMALISASI DALAM PENGELOLAAN RUANG TERBUKA HIJAU PUBLIK TAMAN KOTA DI KOTA BANJARBARU - Forasidah, Forasidah (stiatabalong.ac.id, 2021)
This study aims to: (1) Know the form of the government's response to the optimization of Green Open Space Management in the City of Banjarbaru. (2) Knowing the Public Understanding of Green Open Space Management in Banjarbaru City. And (3) Knowing what are the guardians of improving the optimization of Green Open Space Management in the City of Banjarbaru. This research refers to the management indicators of J George R Terry's theory, while the method used in this research is a mixed method using a sequential type of explanation design, where in this study collect and analyze qualitative data then collect and analyze quantitative data. The results of research on optimization in the management of public green open spaces in city parks in Banjarbaru City have been running